The Role of Midwives and Traditional Birth Attendant Partnership Program in Empowering Traditional Birth Attendant to Improve Maternal Health in Klaten, Central Java - Panuntun, Sri; Karsidi, Ravik; Murti, Bhisma; Akhyar, Muhammad (Journal of Maternal and Child Health, 2019)
Background: It cannot be denied that the dependence of pregnant women on the knowledge, knowledge and experience of traditional birth attendant is still very high. Traditional birth attendants are considered as figures who have abilities related to local culture. On the other hand midwives are the most well-known health care workers to rural areas, have medical knowledge, knowledge and technology, on average young, but have not fully gained public trust. Subjects and Method: This was a qualitative study with case study approach. The study was conducted in North Klaten District, Klaten Regency, Central Java. Results: Traditional birth attendants were people who were trusted by the community to have knowledge and experience in the health of pregnancy. Partnership Guidelines for Midwives and traditional birth attendant issued by the Ministry of Health are divided into stages of pregnancy, and childbirth. Conclusion: The implementation of midwive and TBA partnership in accordance with govern